Electoral Accountability in a Multilevel Governance Context: Economic Voting and Gubernatorial Support in Latin America - François Gélineau; Mathieu Turgeon; Yannick Dufresne; Axel Déry (Journal of Politics in Latin America)
We know a great deal about how individual and institutional factors combine to explain economic voting in well-established democracies, but much less is known about these dynamics in younger democracies and even less so in subnational contexts. Using survey and fiscal data from four federal Latin American countries and adopting a multilevel estimation strategy, we examine voters’ ability to blame and reward governors for the state of the economy (state and national levels) while simultaneously accounting for the states’ level of fiscal centralization and partisan dynamics between the two levels. We find that support for governors is weakly associated with the economy but more strongly so with presidential approval. More importantly, we find that fiscal centralization and partisan dynamics moderate the association between the economy, presidential approval, and support for governors. Little support is found, however, for the clarity of responsibility argument in multilevel governance in these Latin American countries.